Trends in the choice of personal names in Latvia and other Baltic countries: a comparative aspect - Balode, Laimute (Vilnius University Open Series, 2022)
The article deals with the recent tendencies of the names given to new-borns in Latvia during the last 18 years. This study provides a short comparison between the contemporary anthroponymic stock and the historical data, i.e., with the most popular names 100 years ago – at the beginning of the 20th century. Nowadays newborns are given two or even three names. An inherited name in the family has often been chosen as a second name, even more frequently the second name reflects national identity – especially in mixed families. More and more parents choose international, easily pronounced, short names, preferably without diacritical marks. The number of new borrowed foreign first names increased rapidly not only in Latvia, but in all Baltic countries. One of the motivations for the newborn’s name is originality: a lot of neologisms based on Latvian/Lithuanian/Estonian appellatives, mostly with the primary semantics of nature, have been coined. Quite often the names change their gender. Whereas the diminutive forms as official names in Latvia and Lithuania are not popular anymore. It is rather fashionable to give the first names of toponymic origin. The article also presents public attitudes towards these changes. A short overview on the comparison of the latest tendencies in the neighbouring countries – Lithuania, Estonia and Finland – is given as well.
Keywords: onomastics; anthroponymy; given names; identity; Latvia; Baltic countries